# -x=2x^2-6

## Simple and best practice solution for -x=2x^2-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for -x=2x^2-6 equation:

Simplifying
-1x = 2x2 + -6

Reorder the terms:
-1x = -6 + 2x2

Solving
-1x = -6 + 2x2

Solving for variable 'x'.

Reorder the terms:
6 + -1x + -2x2 = -6 + 2x2 + 6 + -2x2

Reorder the terms:
6 + -1x + -2x2 = -6 + 6 + 2x2 + -2x2

Combine like terms: -6 + 6 = 0
6 + -1x + -2x2 = 0 + 2x2 + -2x2
6 + -1x + -2x2 = 2x2 + -2x2

Combine like terms: 2x2 + -2x2 = 0
6 + -1x + -2x2 = 0

Factor a trinomial.
(3 + -2x)(2 + x) = 0

Subproblem 1Set the factor '(3 + -2x)' equal to zero and attempt to solve:

Simplifying
3 + -2x = 0

Solving
3 + -2x = 0

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -2x = 0 + -3

Combine like terms: 3 + -3 = 0
0 + -2x = 0 + -3
-2x = 0 + -3

Combine like terms: 0 + -3 = -3
-2x = -3

Divide each side by '-2'.
x = 1.5

Simplifying
x = 1.5
Subproblem 2Set the factor '(2 + x)' equal to zero and attempt to solve:

Simplifying
2 + x = 0

Solving
2 + x = 0

Move all terms containing x to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + x = 0 + -2

Combine like terms: 2 + -2 = 0
0 + x = 0 + -2
x = 0 + -2

Combine like terms: 0 + -2 = -2
x = -2

Simplifying
x = -2Solutionx = {1.5, -2}`